Addressing the Current Knowledge and Gaps in Research Surrounding Lysergic Acid Diethylamide (LSD), Psilocybin, and Psilocin in Rodent Models - Ezeaka, Udoka C.; Kim, Hye Ji J.; Laprairie, Robert B. (Current Topics in Medicinal Chemistry, 2023)
Lysergic acid Diethylamide (LSD), psilocybin, and psilocin are being intensively evaluated as potential therapeutics to treat depression, anxiety, substance use disorder, and a host of other psychiatric illnesses. Pre-clinical investigation of these compounds in rodent models forms a key component of their drug development process. In this review, we will summarize the evidence gathered to date surrounding LSD, psilocybin, and psilocin in rodent models of the psychedelic experience, behavioural organization, substance use, alcohol consumption, drug discrimination, anxiety, depression-like behaviour, stress response, and pharmacokinetics. In reviewing these topics, we identify three knowledge gaps as areas of future inquiry: sex differences, oral dosing rather than injection, and chronic dosing regimens. A comprehensive understanding of LSD, psilocybin, and psilocin’s in vivo pharmacology may not only lead to their successful clinical implementation but optimize the use of these compounds as controls or references in the development of novel psychedelic therapeutics.
Keywords: Lysergic acid Diethylamide (LSD)